Embryonic stem-like cells derived from in vitro produced bovine blastocysts - Freitas,Erika Regina Leal de (2011)
The aim of this work was to study the derivation of bovine embryonic stem-like (ES-like) cells from the inner cell mass (ICM) of in vitro produced blastocysts. The ICMs were mechanically isolated and six out of seventeen (35%) ICMs could attach to a monolayer of murine embryonic fibroblasts (MEF). Ten days after, primary outgrowths were mechanically dissected into several small clumps and transferred to a new MEF layer. Cells were further propagated and passaged by physical dissociation over a 60 days period. The pluripotency of the bovine ES-like cells was confirmed by RT-PCR of Oct-4 and STAT-3 gene markers. The colonies were weakly stained for alkaline phosphatase and the mesoderm and endoderm differentiation gene markers such as GATA-4 and Flk-1, respectively, were not expressed. Embryoid bodies were spontaneously formed at the seventh passage. Results showed that bovine ES-like cells could be obtained and passaged by mechanical procedures from the fresh in vitro produced blastocysts.